Whatsapp Language is Devastation of Original Languages: Exploring the Impact of Whatsapp on the English Language (Journal of Advances and Scholarly Researches in Allied Education, 2019)
WhatsApp as a matter of course pursues the language of your phone. This implies on the off chance that you change the language of your phone from English to German, the application will consequently be in German. WhatsApp needs you to visit more and it ensures that language is no hindrance in it. This is the motivation behind why the talk application is accessible in excess of 40 languages and up to 60 on Android over the globe. Mobile phone use and telecommunication has been one of the runaway accomplishments of the twenty-first century. Be that as it may, the question which baffles us at EF English Live is – has it influenced the manner in which we utilize the language of English? And on the off chance that it has, is it for better or in negative ways? An UN survey in 2012 found that at the hour of surveying a little more than a year back, there were the same number of mobile phones as people in the world more than six billion. At the point when you think about that around half of that worldwide populace lives in a state of subsistence or destitution which makes owning a mobile phone improbable, those measurements are much progressively mind blowing. The purpose of this paper is to find out the effect of using the Whatsapp messages on the English language.